Book Review: Learning to Leave: The Irony of Schooling in a Coastal Community - Paul Theobald (Journal of Research in Rural Education, 2007)
I hadn't spent much time reading Michael Corbett's Learning to Leave before deciding that this was clearly a major research contribution"one that will join a relatively short list of first-rate books aimed at helping the education research community, as well as the general public, understand the convoluted phenomenon known as rural education. Corbett took a geographically bounded context" Nova Scotia's Digby Neck region, a long narrow strip of land jutting into the Bay of Fundy at the far southwest point of the province, forming, as a result, St. Mary's Bay to the east and a stretch of territory that came to be dominated by fishing for centuries"and asked who among local youth stays on "the Neck," who leaves, and what role did formal schooling play in the staying or the leaving?